2020
DOI: 10.3389/fnagi.2020.00068
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-κB Dysregulation and α-Synuclein Pathology: Critical Interplay in the Pathogenesis of Parkinson’s Disease

Abstract: The loss of dopaminergic neurons of the nigrostriatal system underlies the onset of the typical motor symptoms of Parkinson's disease (PD). Lewy bodies (LB) and Lewy neurites (LN), proteinaceous inclusions mainly composed of insoluble α-synuclein (α-syn) fibrils are key neuropathological hallmarks of the brain of affected patients. Compelling evidence supports that in the early prodromal phases of PD, synaptic terminal and axonal alterations initiate and drive a retrograde degeneration process culminating with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 187 publications
(242 reference statements)
3
44
0
Order By: Relevance
“…Akt, NF- κ B, and p38 are dysregulated in the brain of PD patients [ 24 , 50 52 ] and are the main components in the signal transduction pathway predominantly responsible for the generation of ROS and proinflammatory factors [ 53 ]. To investigate how MEs affect ROS and neuroinflammation in MPTP-induced PD mice, the effect of MEs on the phosphorylation of Akt, NF- κ B, and p38 in the striatum was measured.…”
Section: Resultsmentioning
confidence: 99%
“…Akt, NF- κ B, and p38 are dysregulated in the brain of PD patients [ 24 , 50 52 ] and are the main components in the signal transduction pathway predominantly responsible for the generation of ROS and proinflammatory factors [ 53 ]. To investigate how MEs affect ROS and neuroinflammation in MPTP-induced PD mice, the effect of MEs on the phosphorylation of Akt, NF- κ B, and p38 in the striatum was measured.…”
Section: Resultsmentioning
confidence: 99%
“…iNOS is only expressed under pathological conditions and catalyzes L-arginine to NO, and iNOS is closely associated with vascular inflammation ( 56 ). The NF-κB family is composed of p65, p50, p52, RelB and c-Rel, which combine to form transcriptionally active dimers ( 57 ). After activation, p65 is transported from the cytoplasm to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear factor NF- k B is a protein complex that regulates cytokines production, playing a crucial role in the regulation of inflammation and apoptosis involved in the brain programming of systemic aging, as well as in the pathogenesis of several neurodegenerative diseases, including PD [ 19 ]. In an oxidative condition, NF- k B initiates the transcription of proinflammatory genes coding cytokines and proteolytic enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…However, NF- k B factor is composed by different dimers that can have either protective or noxious effects. For example, p50/RelA dimers induce pro-apoptotic and c-Rel-containing dimers exert neuroprotective actions [ 19 ]. Studies in another PD model also reported dopaminergic neuron loss in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-mouse model suggesting that RelA upregulation may play a role in dopaminergic neuron degeneration when RelA is subexpressed [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation